Optimum Distributed Generation Allocation Using PSO in order to Reduce Losses and Voltage Improvement - Ab Ghani, Mohd Ruddin; Hasan, Ihsan Jabbar; Gan, Chin Kim (2014)
The technology advancement in Distributed Generations (DG) has significantly influenced the environmental pollution. In power system, more especially in distribution networks, DGs can able to mitigate the total losses of the network which effectively has significant effects on environmental pollution. Optimal location and size of DG in distribution networks is one of the important issues of the power system. This paper aims to investigate the best solution for optimal operation of distribution networks by taking into consideration of DG. The optimal allocation of DG can be considered as an integer problem that can be formulated by met heuristic methods. In this paper, the Particle Swarm Optimization (PSO) algorithm has been used to solve the DG placement and sizing. The IEEE 34 bus test system has been utilized to demonstrate the effectiveness of the PSO algorithm on herein mentioned problem. The result illustrates the losses minimization and voltage profile improvement.